Pengaruh Kompensasi Terhadap Motivasi Kerja Karyawan Pada Rumah Sakit Dirgahayu Samarinda - Nentang, - Yulita (EKONOMIA, 2019)
This studsy aims to explain how compensation effects the work motivation of the workers in Dirgahayu Hospital.The tools of analysis used in this study is simple Linear Regression Analysis that can be used to predict the significance of the function or causality between a dependent variable (Y) that is work motivation and an independent variable (X) which is compensation. The function of Linear Regression can be shown as: Y=a + bxPartial test results gives the value of tcount as 4,779 with a 0,017 significance value, meanwhile the ttable shows a value of 1,985. Because tcount > ttable, with a the significance value being less than 0,05, therefore the H1 hypothesis is true, meaning that compensation has a significant, positive impact on work motivation. From the results of the calculation of determination coefficient, the value of r square value in the regression model is 0,884. This shows that can be explained by this equation is 88,40% while the remaining 11,60% is influenced by other factors included in this research